Mobile tax base as a global common - Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2007)
If countries anticipate Bertrand competition in tax rates, they may expend effort that makes some of their tax payers less mobile or increases the mobility of tax payers elsewhere. I provide piecemeal evidence on what activities countries use. I analyse how such activities interact with Bertrand tax competition if the size of the group of loyal and non-loyal citizens or investors is endogenous. Further I consider the implications of tax harmonization and minimum taxes for these types of non-price competition. Home attachment reduces the intensity of tax competition, but generates a strategic disadvantage for the country that invests much in such home attachment. Harmonization of taxes and high minimum taxes can intensify countries' investment in home attachment.
Keywords: H77; F21; F22; 330; tax competition; common pool; advertizing; nation brands; instilling preferences; home bias; patriotism; Steuerwettbewerb; Duopol; Internationale Arbeitsmobilität; Steuerharmonisierung; Optimale Besteuerung; Zwei-Länder-Modell; Theorie